Integrative 5-Methylcytosine Modification Immunologically Reprograms Tumor Microenvironment Characterizations and Phenotypes of Clear Cell Renal Cell Carcinoma - Xu, Wenhao; Zhu, Wenkai; Tian, Xi; Liu, Wangrui; Wu, Yuanyuan; Anwaier, Aihetaimujiang; Su, Jiaqi; Wei, Shiyin; Qu, Yuanyuan; Zhang, Hailiang; Ye, Dingwei (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment (TME) affects the biologic malignancy of clear cell renal cell carcinoma (ccRCC). The influence of the 5-methylcytosine (m5C) epigenetic modification on the tumor microenvironment is unknown. We comprehensively assessed m5C modification patterns of 860 ccRCC samples (training, testing and real-world validation cohorts) based on 17 m5C regulators and systematically integrated the modification patterns with TME cell-infiltrating characterizations. Our results identified distinct m5C modification clusters with gradual levels of immune cell infiltration. The distinct m5C modification patterns differ in clinicopathological features, genetic heterogeneity, patient prognosis and treatment responses of ccRCC. Elevated m5C.score, characterized by malignant biologic process of tumor cells and suppression of immunity response, implied an immune-desert TME phenotype and was associated with dismal prognosis of ccRCC. Activation of exhausted T cells and effective immune infiltration were observed in the low m5C.score cluster, reflecting a non-inflamed and immune-excluded TME phenotype, with favorable survival and better responses to immunotherapy. Together, these findings provide insights into the regulation mechanisms of DNA m5C methylation modification patterns on the tumor immune microenvironment. Comprehensive assessment of tumor m5C modification patterns may enhance our understanding of tumor microenvironment cell-infiltrating characterizations and help establish precision immunotherapy strategies for individual ccRCC patients.